DAMPAK GUNCANGAN KESEHATAN TERHADAP KONSUMSI RUMAH TANGGA DI INDONESIA: ADAKAH PERAN ASURANSI KESEHATAN DAN KREDIT MIKRO? - Umaroh, Rodhiah; Listiono, Listiono (Jurnal Ekonomi Kesehatan Indonesia, 2023)
This paper aims to analyze the impact of health shock on household consumption and estimate the role of health insurance and microcredit in tackling the shock impact. The primary variable used in this study as a proxy for health shock is the impairment of activity in daily living (ADL) experienced by household heads. The impact evaluation method of Propensity Score Matching (PSM) was employed to estimate the impact of health shock on Indonesian household consumption using data from Indonesian Family Life Survey (IFLS-5). This study's result reveals that health shock significantly reduces household consumption of both food and non-food consumption. Another important finding from this study is health insurance and microcredit can help the household to mitigate the negative impact of health shock. Health insurance and microcredit can be concluded to have an important role as a coping risk mechanism for households in the middle crisis of health shock.